Efektivitas Program Pusaka Sakinah sebagai Preventif dalam Meminimalisir Perceraian pada KUA Kecamatan Stabat Kabupaten Langkat - Muhammad Hafiz; Sudianto Sudianto; Azhar Azhar (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Marriage is a bond of body and soul between a man and a woman as husband and wife, with the aim of forming a happy family based on the belief in the One and Only God. In married life, husband and wife must build a positive and harmonious interaction pattern so that a harmonious family can be created. The government instructed the Ministry of Religious Affairs through the Director General of Islamic Community Guidance in 2019 by issuing regulations on the implementation of the Sakinah Heritage program, which is motivated by the high divorce rates in Indonesia due to economic factors, disputes, and incessant quarrels. In this research, the researcher has two problem formulations: 1) What is the effectiveness of the Sakinah Heritage program at the Office of Religious Affairs in Stabat District, Langkat Regency? 2) How does the Sakinah Heritage program serve as a preventive measure against divorce among couples in the Stabat District Office of Religious Affairs, Langkat Regency? This study uses a qualitative research method that is empirical in nature, conducting field research with a legal sociology approach and a statute approach. The data sources used in this research are primary data sources in the form of information obtained from several informants, including: the Head of the Office of Religious Affairs in Stabat District, Religious Counselors, Marriage Registrars, and participants of the Sakinah Heritage program, as well as secondary data in the form of documents supporting the primary data. The data collection techniques in this study include observation, interviews, and documentation. The data analysis in this research uses analytical procedures, namely data reduction, data presentation, and verification. The results of this study indicate that the implementation of the Sakinah Heritage program at the Office of Religious Affairs in Stabat District, Langkat Regency, based on the analysis, has been in accordance with the Decree of the Director General of Islamic Community Guidance Number 783 of 2019 concerning Guidelines for Sakinah Family Services. This program is important for couples in the Stabat District Office of Religious Affairs to follow as an alternative government step to prevent divorce, as couples who have participated in the Sakinah Heritage program have been well-prepared to create a resilient and strong family.